Ecosophic Audiovisuals: Environmental education through screens (Revista Contexto & Educação, 2024)
This study deals with a teacher training process in Environmental Education, through the construction of socio-environmental audiovisuals. Information and Communication Technologies (ICTs) were used in a socio-environmental educommunication experience permeated by ecosophy, which project the creation of new existing territories based on the interaction I, the us (socius) and the environment. The objective of this study is to analyze ecosophical socio-environmental audiovisual productions and their potential for the realization of EE. The research methodology is characterized as qualitative and bibliographical, anchored in action research with participant observation. As data training procedures for the use of environments, during the production of audio and transitions of meetings held with teachers, in addition to meetings of two technicians and audiovisual meetings for different environments of training of four teachers and basic education. The environmental results in the space of school opportunities and a socio-environmental strategy of environmental education of educational modes are a socio-environmental strategy that offers different possibilities, while the different means of Environmental Education.
Keywords: Environmental Education; Training with teachers; Audiovisual; Ecosophy